Exploration of Ndikkar and Tortor's Movements in the Performance Before I Forget You Pt I - Sari, Melati Pravita; Rifandi, Ilham; Rahmatika, Aulia (Institut Seni Indonesia Padangpanjang, 2023)
This article discusses how to use basic cultural body movements as basic material in creating the performance Before I Forget You Pt I. This performance is one of the repertoires from Aka Bodi Theater which is being performed at the Jong Batak Arts Festival in 2023. This performance is the result of a collaboration between young artists The city of Medan carries a diversity of cultural identities, from the initiator to the performer, so the basic body materials used are also diverse. Specifically, this article discusses how to explore the basic movements used, such as the Ndikkar movement from the Karo ethnic group and the Tortor movement from the Toba Batak ethnic group. This research uses qualitative research methods to find an in-depth understanding of the process of creating the work. Therefore, the results of this research will be related to the process of exploring Ndikkar and Tortor's movements in the Before I Forget You Pt I performance.